Incentivizing Monitoring and Compliance in Trophy Hunting - Bunnefeld,N; Edwards,CTT; Atickem,A; Hailu,F; Milner-Gulland,EJ (Conservation Biology, 2013)
Conservation scientists are increasingly focusing on the drivers of human behavior and on theimplications of various sources of uncertainty for management decision making. Trophy hunting has beensuggested as a conservation tool because it gives economic value to wildlife, but recent examples show thatoverharvesting is a substantial problem and that data limitations are rife. We use a case study of trophyhunting of an endangered antelope, the mountain nyala (Tragelaphus buxtoni), to explore how uncertaintiesgenerated by population monitoring and poaching interact with decision making by 2 key stakeholders: thesafari companies and the government. We built a management strategy evaluation model that encompassesthe population dynamics of mountain nyala, a monitoring model, and a company decision making model. Weinvestigated scenarios of investment into antipoaching and monitoring by governments and safari companies.Harvest strategy was robust to the uncertainty in the population estimates obtained from monitoring, butpoaching had a much stronger effect on quota and sustainability. Hence, reducing poaching is in the interestsof companies wishing to increase the profitability of their enterprises, for example by engaging communitymembers as game scouts. There is a threshold level of uncertainty in the population estimates beyond whichthe year-to-year variation in the trophy quota prevented planning by the safari companies. This suggests a rolefor government in ensuring that a baseline level of population monitoring is carried out such that this levelis not exceeded. Our results illustrate the importance of considering the incentives of multiple stakeholderswhen designing frameworks for resource use and when designing management frameworks to address theparticular sources of uncertainty that affect system sustainability most heavily.